Psychophysiological Analysis of Correction Calculation for as Turbine Engine Gas Turbine Engine Noise Tonality - Volodymir M. Zhuravlev; Igor F. Kravchenko; Sergiy V. Dmytriyev (Engineering Proceedings, 2025)
In this paper, we duct a psychophysiological and methodological analysis of the calculation of tonality correction during bench tests of aircraft gas turbine engines for compliance with environmental noise requirements. It is proven that the noise characteristics of a signal are influenced by the modulation law of its tonal components. It is shown that the application of the spectral analysis method for gas turbine engine acoustic signals, for which the stationarity parameters are not determined, leads to an uncertain systematic error. The calculation of the tonality parameter value, which determines the correction of deterioration of the environmental impact assessment of the engine, is not substantiated and has a random character. This paper presents a methodology for the psychophysiological ranking of gas turbine engine noise signals, which offers an intelligent algorithm for signal processing that corresponds with that corresponds with the speech zones of the human central nervous system.